Evaluating Cognitive Distortion Scale Using Exploratory Factor Analysis and Reliability Analysis - Tan, Yao Xiong; Rizal, Abu Bakar; Mohamad Azhari, Abu Bakar (2020)
Despite being used extensively in suicide research, the psychometric properties of Cognitive Distortion Scale have not been examined in Malaysia. This study aimed to study the reliability and validity of this scale. A study was performed on 414 university students. Participants had to respond for each item based on the scale of 1 (never) to 7 (all the time). The reliability and validity of the instrument were analysed with the Cronbach’s Alpha and Exploratory Factor Analysis using the Statistical Package for Social Sciences (SPSS), version 25. Finding from the reliability analysis suggested high reliability index value with the overall score was 0.94. Further, the result for instrument validity based on the exploratory factor analysis suggested three (3) main constructs with eigenvalue more than 1 which explained 61.36%of variance. The factor loading values for each criterion ranged from 0.47 to 0.86. Overall, finding obtained from this study has shown that Cognitive Distortion Scale has high reliability and validity, and suggested to load ten cognitive patterns into three patterns.